O Controle do uso do solo para proteção dos Mananciais - Moreira, Antonio Claudio M. L. (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1993)
The paper presents the urbanistics effects of the legislation for water resources protection at São Paulo metropolitan area. Furthermore, the policy is ineffective to control the urban bonderings expansion, because it denies the previous preparation for urban use and the characteristics of populational settlement in this area